Exploring Use of Nontraditional Tobacco Products Through Focus Groups with Young Adult Smokers, 2002 - Linda L. Pederson, PhD; Ralph Caraballo, PhD; Nisha Gupta, MPH; Patricia Richter, PhD (Centers for Disease Control and Prevention, 2008)
IntroductionIn 2002, 16 focus groups with young adult smokers who used or had tried nontraditional tobacco products (e.g., bidis, shisha, herbal cigarettes, kreteks, cigars, herbal smokeless products) were conducted in Dallas, Texas, and Chattanooga, Tennessee, to gain an understanding of the appeal of these products. MethodsIn each city, groups were segmented by race or ethnicity and by educational status. ResultsMany consistent themes emerged across the groups. Nontraditional tobacco use is not common among young adult smokers. Although some products such as Black & Mild and Swisher Sweets cigars are used frequently by some groups, other products such as shisha, kreteks, and herbal cigarettes are less well known and infrequently used. Among focus group participants, use of nontraditional tobacco products tends to occur in clubs, during social gatherings, or at times when cigarettes are unavailable. More college students than those who were not in college cited cost and inconvenience of purchasing nontraditional tobacco products as reasons for not using them. All focus group participants agreed that African Americans use cigars more than any other racial or ethnic group. ConclusionOverall, findings suggest that the reasons for trying nontraditional tobacco products did not differ by race or ethnicity. Family members and peers were mentioned as the source of nontraditional tobacco products when first used. Cost, convenience, taste, smell, and strength were given as reasons both for using these products and for discontinuing their use.